Deubiquitinating and Interferon Antagonism Activities of Coronavirus Papain-Like Proteases - Clementz, Mark A. (American Society for Microbiology (ASM), 2010)
Coronaviruses encode multifunctional proteins that are critical for viral replication and for blocking the innate immune response to viral infection. One such multifunctional domain is the coronavirus papain-like protease (PLP), which processes the viral replicase polyprotein, has deubiquitinating (DUB) activity, and antagonizes the induction of type I interferon (IFN). Here we characterized the DUB and IFN antagonism activities of the PLP domains of human coronavirus NL63 and severe acute respiratory syndrome (SARS) coronavirus to determine if DUB activity mediates interferon antagonism. We found that NL63 PLP2 deconjugated ubiquitin (Ub) and the Ub-line molecule ISG15 from cellular substrates and processed both lysine-48- and lysine-63- linked polyubiquitin chains. This PLP2 DUB activity was dependent on an intact catalytic cysteine residue. We demonstrated that in contrast to PLP2 DUB activity, PLP2-mediated interferon antagonism did not require enzymatic activity. Furthermore, addition of an inhibitor that blocks coronavirus protease/DUB activity did not abrogate interferon antagonism. These results indicated that a component of coronavirus PLP-mediated interferon antagonism was independent of protease and DUB activity. Overall, these results demonstrate the multifunctional nature of the coronavirus PLP domain as a viral protease, DUB, and IFN antagonist and suggest that these independent activities may provide multiple targets for antiviral therapies.